Perlindungan Hukum Konsumen Pengguna e-Banking: Ditinjau dari Undang-Undang Perlindungan Konsumen dan Undang-Undang Perbankan - Silvia Wisuda (Postgraduate University of Merdeka Malang, 2022)
The purpose of the research is to analyze the legal protection of e-banking users, and the rules needed to perfect the legal protection of e-banking users. This research is a normative legal research that focuses on literature research. The results show that in Indonesia, e-banking transactions are currently not fully protected. Forms of legal protection for customers/consumers from abuse of circumstances in standard agreements according to Law Number 8 Year 1999. Implementation of consumer protection for e-banking service users is carried out by emphasizing the aspects of e-banking technology security, customer complaints, and consumer education. In terms of technological security, 3 principles are applied, namely confidentiality, integrity and availability. Improvement of consumer protection is done by cooperation, increased coordination, online information exchange and designated contact person by involving various parties to reduce the occurrence of crime against the e-banking system. DOI: https://doi.org/10.26905/mlj.v3i1.9176